Aprendemos a reconocernos y respetarnos en nuestras diferencias para enriquecer nuestras relaciones - Julca Tineo, Milagros Maria (2018)
All people come to the world with characteristics that make us unique And throughout our development we are consolidating the acquisition of our own unique identity in this process we feel two needs that can appear simultaneously and sometimes independently all we have the need to be recognized in our individuality and be differentiated from others and on the other hand to be recognized and treated as equal to others Respect for diversity implies understanding and valuing points of view behaviors and needs of people from all walks of life the ability to value respecting and accepting identities, contexts and differences from those of other people contributes to a more tolerant society as society is more diverse the adolescent will be exposed to people from different contexts .To help prepare it for our changing society, it is necessary to teach them the value of tolerance and diversity. For this reason, learning activities have been developed in the area of family and human relations for the 3rd grade of secondary education called learn to recognize and respect each other in our differences To enrich our relationships so that students recognize that we are all different and we must respect each other in our lifestyle differences of opinions, likes, thoughts, values, etc. Diversity is a characteristic of human groups to recognize and accept diversity and the differences of the people as well as respecting their wishes and expectations is an important step to guarantee the harmonious coexistence between the people with whom we interact daily